The long-term implications of the COVID-19 pandemic and recovery measures on environmental pressures A quantitative exploration - Dellink, Rob (OECD Publishing, 2021)
This paper analyses the long-term effects of the COVID-19 pandemic and associated government responses on the environment. It uses large-scale modelling to investigate the impact of sectoral and regional shocks to the economy until 2040. These detailed economic impacts are linked to a range of environmental pressures, including greenhouse gas emissions, emissions of air pollutants, the use of raw materials and land use change. The short-term reductions in environmental pressures are significant: in 2020, energy-related greenhouse gas and air pollutant emissions dropped by around 7%. Environmental pressures related to agriculture observed a smaller drop in 2020. The reduction in the use of non-metallic minerals, including construction materials, reached double digits. From 2021, emissions are projected to increase again, gradually getting closer to the pre-COVID baseline projection levels as growth rates recover fully. But there is a long-term - potentially permanent - downward impact on the levels of environmental pressures of 1‑3%
Keywords: Environment; Economics